Terenski snežni priročnik Priročnik za izvedbo prereza in preizkusa stabilnosti snežne odeje - Volk Bahun, Manca; Pavšek, Miha (ZRC SAZU, Založba ZRC, 2020)
Avalanches cause the highest number of fatalities in the Alps, threatening many areas and facilities, as well as transport and communications infrastructure. An integral part of avalanche protection is risk communication and warning, which is within the domain of the avalanche service of the Slovenian Environmental Agency. As part of the 'Crossrisk Project', the ZRC SAZU Anton Melik Geographical Institute has prepared a 'Snow Field Manual' which will allow for the standardised collection of field data on snow, snow cover and avalanches. This data forms the basis for determining the current avalanche hazard level. The 'Snow Card' supplement, which is an integral part of the manual, contains a condensed view of the most important contents and also includes two forms (there are a total of 14 forms in the manual) for entering the snow cover cross-section data. It also includes instructions for preparing and performing cross-sections of snow cover and avalanche tests. All information is provided along with a clear explanation key. Finally, a description of typical avalanche problems and types of avalanche hazards follows. The full applicability of the Snow Field Manual and the Snow Card is achieved by entering the digital data of the cross-section and the avalanche test into the appropriate web application.